Quasi-Static and Harmonic Indentation of Osteonal Bone. (28th December 2009) - Huja, S. S.; Hay, J. L.; Rummel, A. M.; Beck, F. M.
Abstract : The purpose of the study was to compare Quasi-Static (QS) and harmonic (CSM) methods of indentation testing. Bone sections were obtained from mid-femoral diaphyses of dogs which received a pair of calcein labels. Labeled ( n = 35) and unlabeled ( n = 112) osteons were identified. Indentation modulus (IM) and hardness (H) for the CSM method were collected during the entire loading cycle to peak depth, while IM and H for QS method were calculated at a peak depth of 500 nm. Results: The mean (SD) of the IM and H for labeled osteons were as follows: QS IM = 15.3 GPa (3.85) versus CSM IM = 14.7 GPa (3.58); P = .52 and QS H = .39 GPa (.171) versus CSM H = .42 GPa (.146); P = .32. The mean (SD) of the IM and H for unlabeled osteons were as follows: QS IM = 21.5 GPa (2.80) versus CSM IM = 20.6 GPa (2.53); P = .054 and QS H = .64 GPa (.117) versus CSM H = .70 GPa (.120); P = .017. There was no difference in IM and H for the two methods, except for H of the unlabeled osteons. In addition, for the CSM method, IM at 100 nm, 200 nm, 300 nm, 400 nm and 500 nm were not statistically significant different ( P = .06). Bone is viscoelastic at an organ level. However, this component of its behavior was not detected at the length scale examined.